Solving the Kuramoto-Sivashinsky equation via Variational Iteration Method - Yousif, majeed Ahmed; Manaa, Saad A.; Easif, Fadhil H. (International Journal of Applied Mathematical Research, 2014)
In this study, the approximate solutions for the Kuramoto-Sivashinsky equation by using the Variational Iteration Method (VIM) are obtained. Comparisons with the exact solutions and the solutions obtained by the Homotopy Perturbation Method (HPM), the numerical example show that the Variational Iteration Method (VIM) is accurate and effective and suitable for this kind of problem. Keywords: Kuramoto-Sivashinsky equation, Variational Iteration Method.